Heterostructured composite of NiFe-LDH nanosheets with Ti4O7 for oxygen evolution reaction. (June 2022) - Ibrahim, K.B.; Su, W.-N.; Tsai, M.-C.; Kahsay, A.W.; Chala, S.A.; Birhanu, M.K.; Lee, J.-F.; Hwang, B.J.
Abstract: Developing oxygen evolution reaction (OER) electrocatalyst based on earth-abundant materials holds great promise for ascertaining water-splitting to surmount its deprived kinetics. In this regard, NiFe-LDH (layered double hydroxide) receives considerable attention owing to their layered structure. However, they still suffer from poor electronic conductivity and structural stability. We combined NiFe-LDH nanosheets with Magnéli phase Ti4 O7 into a heterostructured composite. A series of analyses reveal that decorating Ti4 O7 facilitates charge transfer to enhance the conductivity of NiFe-LDH-Ti4 O7 . During electrochemical measurement, Ni 2+ is transformed to metastable Ni 3+ (Ni (OH)→ NiOOH) before the OER onset potential. Thus, the presence of Ni 3+ as the main active sites could improve the chemisorption of OH − to facilitate OER. As a result, the NiFe-LDH-Ti4 O7 catalyst delivers as low as onset potential (1.43 V). Combining the holey structure (NiFe-LDH and Ti4 O7 ) and the defect engineering generated on NiFe-LDH-Ti4 O7 as a synergistic effect improves the OER performance. The inclusion of Ti4 O7 in the composite leads to more vacancy sites, as evidenced by the extended X-ray absorption fine structure (EXAFS) analysis. The obtained defective structure with a low coordination environment would improve the electronic conductivity and facilitate the adsorption process of H2 O onto metal cations, thereby increasing the intrinsic catalytic activity of NiOOH. The strong coupling of NiFe-LDH and Ti4 O7 also increases the stability, and the heterostructured composite helps maintain the structural robustness of the LDH. Graphical abstract: Image 1 Highlights: Decorating Ti4 O7 to NiFe-LDH creates metal and oxygen vacancies to the hybrid. Ti4 O7 improves the conductivity of the NiFe-LDH and its OER performance. The composite electrocatalyst has only an onset potential of 1.43 V for OER. Decoration of Ti4 O7 prevents LDHs from stacking and results in enhanced stability. Charge transfer between Ti4 O7 and NiFe-LDH was confirmed by XPS and XAS analyses.